1997
DOI: 10.1159/000262393
|View full text |Cite
|
Sign up to set email alerts
|

Rise and Fall of Caries Prevalence in German Towns with Different F Concentrations in Drinking Water

Abstract: The rise and fall of caries prevalence (DMFT) and its relation to changing F concentration of drinking water and other health-related factors is analysed based on dental findings of more than 286,000 subjects of either sex (6–15 years old) from the two industrial towns Chemnitz and Plauen. Water fluoridation (1.0 ± 0.1 ppm F) was implemented in Chemnitz (formerly Karl-Marx-Stadt) in 1959. It was in operation until autumn 1990 with an interruption lasting 22 months around the year 1971. In the F-poor town of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 3 publications
4
50
0
1
Order By: Relevance
“…Already at a low level, caries prevalence decreased even further. This trend was statistically documented for the fluoridated cities Chemnitz (formerly KarlMarx-Stadt) and Plauen [Künzel and Fischer, 1997] and for Spremberg and Zittau [Künzel, 1997]. The observations are also in agreement with those made by Kalsbeek and Verrips [1990] after the cessation of water fluoridation in Tiel/Culemborg.…”
supporting
confidence: 64%
See 1 more Smart Citation
“…Already at a low level, caries prevalence decreased even further. This trend was statistically documented for the fluoridated cities Chemnitz (formerly KarlMarx-Stadt) and Plauen [Künzel and Fischer, 1997] and for Spremberg and Zittau [Künzel, 1997]. The observations are also in agreement with those made by Kalsbeek and Verrips [1990] after the cessation of water fluoridation in Tiel/Culemborg.…”
supporting
confidence: 64%
“…As in recent experiences in East German towns [Künzel and Fischer, 1997], caries prevalence in La Salud remained stable at a low level after the cessation of water fluoridation. A similar development has been reported for the Czech capital Prague [Lekesová et al, 1996], where reduced caries prevalence of 1.8 DMFT of 12-year-olds, due to water fluoridation, remained stable (i.e.…”
Section: Caries Prevalencesupporting
confidence: 52%
“…Cross-sectional study after 5 years Attwood & Blinkhorn 1991Scotland, 1983 dmft, DMFT 3 years after Caries prevalence in no-longer-fluoridated fluoridation ceased community increased and was almost equal to that of non-fluoridated control community. Künzel & Fischer 1997, Germany, 1990 6 to 15 Cross-sectional Caries decline in no-longer-fluoridated Künzel et al, 2000 DMFT community to lowest recorded level. Substantial confounding factors were introduced at the public health level and in the health care delivery models.…”
Section: Multivariate Modelmentioning
confidence: 99%
“…Some reports from settings still affected by relatively high caries activity have indicated that, after fluoridation was discontinued, caries experience increased [Stephen et al, 1987;Attwood and Blinkhorn, 1991;Thomas et al, 1995]. This assessment, however, is problematic when such discontinuation takes place in communities where caries prevalence was declining [Kalsbeek et al, 1993;Künzel and Fischer, 1997;, particularly if the study design encompassed several cross-sectional samples [Maupomé et al, 2001]. A recent study that investigated a temporary cessation of fluoridation found that an 11-month break had little effect on caries in primary molars [Burt et al, 2000].…”
mentioning
confidence: 99%
“…However, the caries decline coincided with several other trends, including the introduction of fluoridated salt in 1992, a decrease in national sugar consumption in 1993 (down to 1967 levels of intake), and complete restructuring of the dental care system after reunification. [12] A further study of other former East German cities suggested that the caries decline was unlikely to be caused by any one single factor, but that the availability of topical fluorides probably had the greatest impact. The authors concluded that for Germany "from our point of view, water fluoridation would still seem to be reasonable in all heavily-populated industrial areas with high or increasing caries prevalence."…”
Section: Fluoridation Around the Worldmentioning
confidence: 97%